2013
DOI: 10.4322/polimeros.2013.033
|View full text |Cite
|
Sign up to set email alerts
|

Separación de fases y cristalinidad en mezclas epoxy/poli-3-hidroxibutirato

Abstract: CONICETResumen: En este trabajo se estudiaron mezclas epoxy/poli-3-hidroxibutirato (PHB) en dos proporciones distintas 90/10 y 85/15. Para ello se prepararon muestras sometiéndolas a temperaturas de 80 °C y 120 °C, a efectos de producir el curado del epoxy. Se analizó la separación de fases y la cristalización del PHB mediante microscopía óptica y calorimetría diferencial de barrido. Asimismo la estructura lamelar del PHB se caracterizó mediante dispersión de rayos X de bajo ángulo. Se encontraron diferencias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Since the values of L for blends with the lowest weight average molecular weight of PS are considerably higher than in other blends, but the crystalline fraction remains almost constant (47.9% ± 1.4% and 53.5% ± 0.7% for T c = 30°C and T c = 40°C, respectively, see Table ), it is possible to conclude that L values do not correlate with an increase in the crystallinity. In Epoxy/PHB blends cured at 80°C and 120°C, by Tognana et al observed a similar behavior. While the crystalline fraction of the blends cured at 120°C was 25% and the crystalline fraction of blends cured at 80°C was 56%, values of L = 19.8 nm for T m = 120ºC, considerably higher that L = 5.5 nm for T m = 80°C, were reported.…”
Section: Resultsmentioning
confidence: 67%
“…Since the values of L for blends with the lowest weight average molecular weight of PS are considerably higher than in other blends, but the crystalline fraction remains almost constant (47.9% ± 1.4% and 53.5% ± 0.7% for T c = 30°C and T c = 40°C, respectively, see Table ), it is possible to conclude that L values do not correlate with an increase in the crystallinity. In Epoxy/PHB blends cured at 80°C and 120°C, by Tognana et al observed a similar behavior. While the crystalline fraction of the blends cured at 120°C was 25% and the crystalline fraction of blends cured at 80°C was 56%, values of L = 19.8 nm for T m = 120ºC, considerably higher that L = 5.5 nm for T m = 80°C, were reported.…”
Section: Resultsmentioning
confidence: 67%